The Influence Of Financial Behavioral Bias In Investment Decisions Of Generation Z Investors In The Capital Market: The Moderating Role Of Financial Self-Efficacy (A Study Of Generation Z Investors In Yogyakarta) - Alifia Nayara Labiba; Sutrisno Sutrisno (UNIVED Press, 2025)
Technological advances make various information more accessible, including information about investment. However, investment usually involves large funds so that investors must be careful and capable, and for years various generations have contributed to investment. Of the various generations, Generation Z (born 1997 - 2012) is dominated because this generation is considered very skilled with technology, making it very easy for them to access the information. However, there are various obstacles that arise, such as their lack of skill in making decisions in investors to psychological factors and investment behavior (availability bias, loss aversion bias, and confirmation bias). Although these factors can be overcome with self-efficacy from several existing references, this still needs to be proven further. With these problems, a quantitative study using the SEM-PLS analysis method was conducted to determine the direct effect of availability bias, loss aversion bias, and confirmation bias on investment decisions and the moderating effect of self-efficacy of Generation Z investors in the Special Region of Yogyakarta (DIY). The research findings are that only loss aversion and confirmation bias have a positive and significant direct effect on investment decisions of Gen Z investors in the DIY capital market. While the three types of behavioral bias (availability, loss aversion, and confirmation bias) only show a positive but insignificant effect on investment decisions when moderated by self-efficacy.